Le Fort III osteotomy for severe dentofacial deformity correction associated with hypoplasia of the midface - SEBASTIANI,Aline Monise (2016)
ABSTRACT The combination of orthodontic therapy and orthognathic surgery is a well-established treatment modality for the correction of dentofacial deformities. When these deformities are more severe, involving hypoplastic midface, surgical techniques not used routinely in the treatment of facial changes are required, such as the Le Fort III osteotomy or variations of this technique. Few studies have reported the use of this technique or its modifications in non-syndromic patients. This paper demonstrates the orthodontic-surgical resolution of a patient with dentofacial deformity with severe malocclusion Class III, involving midface hypoplasia, with a modification technique of a Le Fort III osteotomy associated with Le Fort I and sagittal of the rami osteotomies. After three years of postoperative follow-up, the patient demonstrates significant improvement in chewing ability, no functional complaints, and high satisfaction with the aesthetics and improved quality of life.